Apartments - Lumbao Jr., Cocoy (Likhaan: The Journal of Contemporary Philippine Literature; Vol 17 No 1 (2023): LIKHAAN 17: The Journal of Contemporary Philippine Literature, 2023)
Two young lovers rendezvous in one of the old apartment units in Santa Mesa to escape the sweltering midday heat. This idle moment paves the way for exploring the nature of what seems like pure, youthful romance, before the view explodes to reveal the complexities and incertitudes behind their relationship. This is a portrait of two lives navigating the pressures of city-life, or the demands of a specific place–-conveyed in prose that tries to capture its own convoluted nature.